Mutation mapping of the 2B5 ecdysone locus in Drosophila melanogaster reveals a long-distance controlling element. - Sampedro, J.; Galceran, J.; Izquierdo, M. (Molecular and Cellular Biology, 1989)
Mutations at the Broad-Complex, a key gene triggering metamorphosis in Drosophila melanogaster, were mapped at the DNA level. The Broad-Complex includes two mutually complementing allelic classes, br and l(1)2Bc, both of which can associate to insertions at the same intron. Alterations spreading over 50 kilobases upstream from the transcription unit also disrupt br but not l(1)2Bc function.